2017
DOI: 10.1097/pgp.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa Cell Tumors: Novel Predictors of Recurrence in Early-stage Patients

Abstract: Summary: Granulosa cell tumors (GCTs) comprise 2% to 5% of ovarian neoplasms, with unpredictable patterns of recurrence. The HER family, GATA4, and SMAD3 genes are reportedly involved in GCT proliferation and apoptosis and may serve as new predictors of recurrence. The aim of the study was to evaluate novel predictors of recurrence in GCT from a large single institution cohort. Patients diagnosed with GCTs (n = 125) between 1975 and 2014 were identified. Clinicopathologic parameters were obtained and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Also, GCT recurrence remains largely unpredictable, although this risk may be increased by factors such as patient's age, tumor size >10 to >15 cm, intraoperative tumor rupture and genetic [ [16] , [17] , [18] ]. Recurrences after therapy have typically occurred within 5 to 10 years [ 19 ]. Therefore, we suggest following up every 3 months in endocrine clinic about regression of puberty signs and symptoms and at least every 6 months laboratory tests and pelvic ultrasound be done.…”
Section: Discussionmentioning
confidence: 99%
“…Also, GCT recurrence remains largely unpredictable, although this risk may be increased by factors such as patient's age, tumor size >10 to >15 cm, intraoperative tumor rupture and genetic [ [16] , [17] , [18] ]. Recurrences after therapy have typically occurred within 5 to 10 years [ 19 ]. Therefore, we suggest following up every 3 months in endocrine clinic about regression of puberty signs and symptoms and at least every 6 months laboratory tests and pelvic ultrasound be done.…”
Section: Discussionmentioning
confidence: 99%
“…Sakr et al [ 44 ] evaluated novel predictors of recurrence in GCTs from a single institution cohort of 125 case between 1975 and 2014, found for early-stage (stage I) aGCTs, high expression of SMAD3 was a independent predictors of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a high expression of CD56 or SMAD3 showed a significant prediction of recurrence. 16 It was recently reported that recurrence may be detected noninvasively from circulating plasma cell free DNA in patients with clinical disease via a liquid biopsy for the FOXL2 mutation. 17 …”
Section: Discussionmentioning
confidence: 99%